The Financial Performance Comparation of Private and Government Bank: Rural Bank Case - Widia, Syam; Prananta, Widya (Management Analysis Journal, 2021)
The purpose of establishing rural bank/ Bank Perkreditan Rakyat known as BPR is to improve the regional economy through credit as financial support for inclusive society. Meanwhile, the contribution of BPR/BPRS (Conventional/Sharia) owned by the Local Government to the regional economy is still small in number. It reflected in the share of productive loans/financing channeled by Local Government BPR lower than private BPR/BPRS. This study aims to Analyze Performance Difference in Private Rural Banks and Rural Banks Owned by Local Government in Central Java Province using financial performance ratios. The financial performance ratios were Capital Adequacy Ratio (CAR), Quality of earning assets, Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Return on Assets (ROA). The method used to analyze data is Different Tests using Independent T-test. This study used SPSS Version 23 analysis tool. The sample of this research is BPR owned by Local Government of Central Java, and Private owned BPR in Central Java Province from 2016 to 2019. Selection of sample by using purposive sampling. Based on Independent T-Test, there is a difference in the ratio of Quality of earning assets and LDR between BPR owned by Local Government and Private Rural Bank, while for the ratio of NPL, CAR, and ROA there is no difference.